2018
DOI: 10.1016/j.ast.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Attitude controller design for reusable launch vehicles during reentry phase via compound adaptive fuzzy H-infinity control

Abstract: In this paper, the attitude control problem of reusable launch vehicles (RLVs) during reentry phase is investigated by using compound adaptive fuzzy H-infinity control (CAFHC) strategy in the presence of parameter uncertainties and external disturbances. Firstly, the control-oriented attitude model is established by a model transformation based on the six-degree-of-freedom(6-DoF) dynamic model of the RLV. Secondly, a novel attitude control scheme is developed and the control strategy consists of two parts to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…To the best of the authors' knowledge, no previous work has implemented a FS approximator in parallel to a WNN approximator, and combined the outputs of the two approximators using the modulation technique that was proposed by Ghavidel and Kalat [26], Ghavidel [27], Dian et al [28], Mao et al [29] as shown in Fig. 3.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, no previous work has implemented a FS approximator in parallel to a WNN approximator, and combined the outputs of the two approximators using the modulation technique that was proposed by Ghavidel and Kalat [26], Ghavidel [27], Dian et al [28], Mao et al [29] as shown in Fig. 3.…”
Section: Introductionmentioning
confidence: 99%
“…The fuzzy logic system (FLS) control method has been attached much attention during the past few years. Because FLS technique is an effective method to deal with the model uncertainties and nonlinear parts of the control system due to its good approximation, thus it has been extensively applied to design the flight control system for the vehicle . In order to enhance the tracking performance and achieve good robustness for the flight control system, FLS has usually been combined with other control approaches such as fault‐tolerant control and adaptive control .…”
Section: Introductionmentioning
confidence: 99%
“…Because FLS technique is an effective method to deal with the model uncertainties and nonlinear parts of the control system due to its good approximation, thus it has been extensively applied to design the flight control system for the vehicle. [24][25][26] In order to enhance the tracking performance and achieve good robustness for the flight control system, FLS has usually been combined with other control approaches such as fault-tolerant control 27 and adaptive control. 28 In addition, a type-2 FLS, which can provide additional design degrees of freedom in Mamdani and Takagi-Sugeno-Kang FLSs, is more effective when such system is used in situations where lots of uncertainties are present compared with type-1 FLS.…”
mentioning
confidence: 99%
“…Many attitude control methods have been proposed for improving the control performance of reentry vehicle. 613 Liang et al. proposed a decoupling trajectory tracking method to improve attitude stability of the reentry vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…10 Among these many proposed attitude control methods, all of them were designed basing on the assumption that the actuator is functioning normally. 613 However, the adverse aerodynamic environment and constantly changing flight condition during the reentry process, makes difficulties for satisfying the assumption as the actuator may be come up with faults like loss of effectiveness, float, etc. If we do not take into account the fault tolerant capability, the reentry may fail or catastrophic accident may happen even though there is only a small actuator fault.…”
Section: Introductionmentioning
confidence: 99%